Optimizing the Synergy of the Three Education Centers in Controlling the Quality of Learning During the Covid-19 Pandemic - Syaifullah, Syaifullah; Suharto, Babun; Fauzi, Imron (Tadbir : Jurnal Studi Manajemen Pendidikan, 2023)
Basically, the synergy of the three education centers in controlling the quality of learning has been well established, but during the Covid-19 pandemic, optimization efforts are needed given the new policies implemented that affect the achievement of learning quality. One of the optimization strategies that can be applied in overcoming this problem is to analyze oneself internally and externally . Through this analysis a solution is obtained that can facilitate the role of the three education centers in synergizing so that the quality of learning can still be achieved. Based on these thoughts, this study aims to dig deeper regarding matters; 1) the role of the three education centers in implementing learning quality control during the Covid-19 pandemic , 2) strategies or steps for optimizing the tri education center synergy, and 3) the impact of optimizing the tri education center synergy in controlling the quality of learning in Situbondo Regency . This study uses a qualitative approach, a case study type. Data was collected using interview techniques, participant observation, and documentation. Data analysis techniques using descriptive analysis and depictions based on percentages. Checking the validity of the data is done through the credibility of the data with a triangulation technique. The findings show that; 1) the role of the three education centers in the implementation of learning quality control during the Covid-19 pandemic needs to be optimized, 2) the strategy or steps for optimizing the synergy of the three education centers is to use a SWOT analysis, by identifying the strengths, weaknesses and opportunities for challenges that exist, and 3) the impact of optimizing the synergy of the three education centers in controlling the quality of learning in Situbondo Regency , students still get learning satisfaction. Although these learning achievements are not in the form of quantitative values as they have been obtained so far, these achievements are qualitative in nature and also have economic value